Analysis of catalytic and non-catalytic regions of the human DNA repair helicase HelQ - Jenkins, T (2021)
Maintaining genome stability is essential to support DNA replication for all life to continue. Multiple systems are in place to ensure this occurs by scrutinising replication as it happens, detecting and repairing changes to DNA caused by damaging agents and removing physical blocks. Repair during replication is essential to ensure errors are not replicated, homologous recombination (HR) is one example; repairing DNA errors by using the homologous template from the sister chromosome. While these pathways exist to maintain genome integrity it is essential that they are tightly regulated to prevent unnecessary activation or downstream impacts on the genome. Therefore, a network of proteins are involved in controlling genome maintenance. Metazoan HelQ DNA helicase is a single- stranded DNA ATPase with 3′ to 5′ translocase activity that unwinds forked DNA structures. It is hypothesised that HelQ activity is crucial in promoting DNA replication and repair through the regulation of HR. However, the mechanism is unknown. While HelQ has shown to co-elute with essential repair proteins including RPA, the Rad51 paralogues and ATR and has been linked to cancer and repair-related diseases, little is known about how HelQ behaves in nature. Here, I was able to generate yields of HelQ and HelQ fragments for biochemical analysis of the recombinant proteins. We show that HelQ forms active dimers that unwind DNA fork substrates but no other intermediate DNA structures. Functional analysis of a catalytically active and non-catalytically active region of HelQ aids in the dissection of HelQ structure and function. I also report that HelQ interacts with the single-stranded DNA binding protein RPA in vitro and the N-terminal ORFan domain is able to displace RPA from DNA through an unknown mechanism. This leads us to hypothesis a model of HelQ activity and translocation on DNA.